Novel Quinolinyl-pyrrolo[3,4-d]pyrimidine-2,5-dione Derivatives Against Chloroquine-resistant Plasmodium falciparum - Rogerio, Kamilla R.; Graebin, Cedric Stephan; Pinto Domingues, Luiza Helena; Oliveira, Luana Santos; de Souza Fernandes da Silva, Vitoria; Daniel-Ribeiro, Claudio Tadeu; Carvalho, Leonardo J.M.; Boechat, Nubia (Current Topics in Medicinal Chemistry, 2020)
Introduction: In this work DHPMs were combined with the quinoline nucleus to obtain new quinolinyl-pyrrolo[3,4-d]pyrimidine-2,5-dione compounds with improved antiplasmodial activity as well as decreased cytotoxicity. Nineteen quinolinyl-pyrrolo[3,4-d]pyrimidine-2,5-dione derivatives connected by a linker group to quinolone ring moieties with different substituents were synthesized and assayed against P. falciparum. Materials and Methods: Nineteen quinolinyl-pyrrolo[3,4-d]pyrimidine-2,5-dione derivatives connected by a linker group to quinoline ring moieties with different substituents were synthesized and assayed against chloroquine-resistant Plasmodium falciparum, along with the reference drug chloroquine. Among these compounds, the derivatives with two methylene carbon spacers showed the best activity accompanied by low cytotoxicity. Results: The derivative without substituents on the aromatic ring (2a) and the derivative with a chlorine group at position 4 (2d) provided the best results, with IC50 = 1.15 μM and 1.5 μM, respectively. Conclusion: Compared to the parent drugs, these compounds presented marked decreases in cytotoxicity, with MDL50 values over 1,000 μM and selectivity indexes of >869.5 and >666.6, respectively. The quinolinyl-pyrrolo[3,4-d]pyrimidine-2,5-dione framework appears to be promising for further studies as an antimalarial for overcoming the burden of resistance in P. falciparum.
Keywords: Malaria